The Effectiveness of Moxibution on Salivary Cortisol Levels in Primiparous Breastfeeding Mothers: Quasi-Experimental Study - Chairunnisa, Miftah; Nurmawati, Thatit; Putri, Raden Roro Dewi Rahmawaty Aktyani (STIKes Patria Husada Blitar, 2025)
Optimal breastfeeding practices play a crucial role in enhancing the health of infants and children. However, increased anxiety among postpartum mothers can lead to higher cortisol levels. Moxibustion is a traditional therapy that has been shown to improve blood circulation, reduce discomfort, and influence the central nervous system by stimulating specific meridian points. This study aimed to examine the effect of moxibustion on cortisol levels in breastfeeding mothers. A quasi-experimental design with pretest and posttest was used. Participants were divided into two groups: an intervention group that received moxibustion and a control group that received acupuncture. A total of 32 breastfeeding mothers from Ngaliyan Public Health Center in Semarang participated in the study, with 16 individuals in each group. Moxibustion was applied to specific meridian points (CV17, LI4, SP6, ST16, ST18, ST36, BL17, and BL18). Cortisol levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method, and data were analyzed using the Mann-Whitney test. The results showed no significant difference in cortisol levels between the two groups (p = 0.864). The average cortisol change was -0.063 in the intervention group and -0.113 in the control group. It was concluded that moxibustion had no significant effect on cortisol levels. Further studies are recommended to explore other factors that may influence cortisol levels in postpartum mothers.